The 5 levels of leadership [compact disc, unabridged] : proven steps to maximize your potential - Maxwell, John C., 1947- (Hachette Audio, 2011)
Describes the five stages of leadership--position, permission, production, people development, and pinnacle--and explains how to attain each level through in-depth explanations and examples.